Identification of lysosomal Npc1‐binding proteins: Cathepsin D activity is regulated by NPC1. Issue 1 (15th December 2015) - Macías‐Vidal, Judit; Guerrero‐Hernández, Martina; Estanyol, Josep Maria; Aguado, Carmen; Knecht, Erwin; Coll, Maria Josep; Bachs, Oriol
Abstract : Niemann–Pick type C (NPC) disease is an inherited lysosomal storage disorder, characterized by severe neurodegeneration. It is mostly produced by mutations in the NPC1 gene, encoding for a protein of the late endosomes/lysosomes membrane, involved in cholesterol metabolism. However, the specific role of this protein in NPC disease still remains unknown. We aimed to identify Npc1‐binding proteins in order to define new putative NPC1 lysosomal functions. By affinity chromatography using an Npc1 peptide (amino acids 1032–1066 of loop I), as bait, we fished 31 lysosomal proteins subsequently identified by LC‐MS/MS. Most of them were involved in proteolysis and lipid catabolism and included the protease cathepsin D. Cathepsin D and NPC1 interaction was validated by immunoprecipitation and the functional relevance of this interaction was studied. We found that fibroblasts from NPC patients with low levels of NPC1 protein have high amounts of procathepsin D but reduced quantities of the mature protein, thus showing a diminished cathepsin D activity. The increase of NPC1 protein levels in NPC cells by treatment with the proteasome inhibitor bortezomib, induced an elevation of cathepsin D activity. All these results suggest a new lysosomal function of NPC1 as a regulator of cathepsin D processing and activity.